COMMAND AND CONTROL OF MAJOR- GENERAL YAKUBU GOWON,1966 – 1970 - Rotimi Olajide Opeyeoluwa; Paul Olusegun Adesanya (International Studies Journal)
The objective of this study is to examine how command and control by Gowon was used in winning the war. In the ensuing years after the war, very scant regard has been accorded to the study of command and control. The concept is one of the areas where there is always a shifting dynamic between command and equipment deployed for military operations.The study relied on secondary and tertiary sources for data. The study submits that despite the initial mis-steps which characterized the military assault by the federal forces, it able to turn the tide of events by command and control under the leadership of General Yakubu Gowon.